Partisipasi Masyarakat Lokal Dalam Pengelolaan Daya Tarik Wisata Pantai Pandawa Di Desa Adat Kutuh Kabupaten Badung - Sugiwinata, Gusti Made; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2018)
This research discusses about Participation of Local Community in the Management of Tourist Attraction of Pandawa Beach at the Customary Village of Kutuh. The research aims to discuss the potential of tourist attraction of Pandawa beach, which has been developed by the authorized management, as well as the participation of local community of Kutuh customary village. Further, the management of tourist attraction of Pandawa Beach is described according to five elements: tourism industry and typology of participation and characteristic of the community. Method used is descriptive qualitative. Data was collected by way of observation, structured interview, literature study and documentation. Later data was analyzed with informant setting technique and purpose sampling technique. Based on the result of discussion can be suggested that local community participation in the management of tourist attraction of Pandawa beach namely the provision of qualifies natural resources, recruitment of employess for tourist attraction of Pandawa beach preferring local population to increase the economy of community of Kutuh customary village.   Keywords : Public Participation Management